The Complete Mitochondrial DNA of Trypanosoma cruzi: Maxicircles and Minicircles - Callejas-Hernández, Francisco (Front Cell Infect Microbiol, 2021)
The mitochondrial DNA of Trypanosomatids, known as the kinetoplast DNA or kDNA or mtDNA, consists of a few maxicircles and thousands of minicircles concatenated together into a huge complex network. These structures present species-specific sizes, from 20 to 40 Kb in maxicircles and from 0.5 to 10 Kb in minicircles. Maxicircles are equivalent to other eukaryotic mitochondrial DNAs, while minicircles contain coding guide RNAs involved in U-insertion/deletion editing processes exclusive of Trypanosomatids that produce the maturation of the maxicircle-encoded transcripts. The knowledge about this mitochondrial genome is especially relevant since the expression of nuclear and mitochondrial genes involved in oxidative phosphorylation must be coordinated. In Trypanosoma cruzi (T. cruzi), the mtDNA has a dual relevance; the production of energy, and its use as a phylogenetic marker due to its high conservation among strains. Therefore, this study aimed to assemble, annotate, and analyze the complete repertoire of maxicircle and minicircle sequences of different T. cruzi strains by using DNA sequencing. We assembled and annotated the complete maxicircle sequence of the Y and Bug2148 strains. For Bug2148, our results confirm that the maxicircle sequence is the longest assembled to date, and is composed of 21 genes, most of them conserved among Trypanosomatid species. In agreement with previous results, T. cruzi minicircles show a conserved structure around 1.4 Kb, with four highly conserved regions and other four hypervariable regions interspersed between them. However, our results suggest that the parasite minicircles display several sizes and numbers of conserved and hypervariable regions, contrary to those previous studies. Besides, this heterogeneity is also reflected in the three conserved sequence blocks of the conserved regions that play a key role in the minicircle replication. Our results using sequencing technologies of second and third-generation indicate that the different consensus sequences of the maxicircles and minicircles seem to be more complex than previously described indicating at least four different groups in T. cruzi minicircles.